(untitled) (Siddhajyoti Interdisciplinary Journal, 2022)
Empowering girls and ensuring gender equality in society is a global aspiration. Education is an important means for girls’ empowerment since it can have multiple effects on girls’ empowerment and gender equality in society. Presently, girls’ enrollment to school education in Nepal seems good; however, their learning achievement is low. This article focuses on the status of girls’ access to school education and their learning achievement. Secondary data have been analyzed to determine the status of girls’ access to school education and their achievement. The study revelas a huge disparity in learning achievement between girls and boys. Girls’ learning achievement is lower than boys and this disparity is deeper with girls from public schools. Improving girls learning achievement needs special attention in the classroom and school to achieve the goal of gender equality and education quality.